Prognostic value of pro-adrenomedullin and copeptin in acute infective endocarditis - Zampino, Rosa (BMC Infect Dis, 2021)
BACKGROUND: Infective endocarditis (IE) is a life-threatening disease whose prognosis is often difficult to predict based on clinical data. Biomarkers have been shown to favorably affect disease management in a number of cardiac disorders. Aims of this retrospective study were to assess the prognostic role of procalcitonin (PCT), pro-adrenomedullin (pro-ADM) and copeptin in IE and their relation with disease characteristics and the traditional biomarker C-reactive protein (CRP). METHODS: We studied 196 patients with definite IE. Clinical, laboratory and echocardiography parameters were analyzed, with a focus on co-morbidities. PCT, pro-ADM and copeptin were measured on stored plasma samples obtained on admission during the acute phase of the disease. RESULTS: Pro-ADM and copeptin were significantly higher in older patients and associated with prior chronic kidney disease. Pro-ADM was an independent predictor of hospital mortality (OR 3.29 [95%C.I. 1.04–11.5]; p = 0.042) whilst copeptin independently predicted 1-year mortality (OR 2.55 [95%C.I. 1.18–5.54]; p = 0.017). A high PCT value was strictly tied with S. aureus etiology (p = 0.001). CRP was the only biomarker associated with embolic events (p = 0.003). CONCLUSIONS: Different biomarkers correlate with distinct IE outcomes. Pro-ADM and copeptin may signal a worse prognosis of IE on admission to the hospital and could be used to identify patients who need more aggressive treatment. CRP remains a low-cost marker of embolic risk. A high PCT value should suggest S. aureus etiology. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12879-020-05655-7.